Penguatan Modal Usaha Mikro, Kecil Dan Menengah Melalui Pembiayaan Di BMT Mandiri Sejahtera Gresik - Heppy Prasetyo Pradhana; Muhammad Nafik H.R (Universitas Airlangga, 2016)
The purpose of this research is to analyze the role of funding by BMT in strengthening the capital of micro, small and medium businesses in BMT Mandiri Sejahtera Gresik. The measure of capital strengthening is viewed by the increase of income, profits, assets and capital structure.This research employed the qualitative approach of using case study. Data collection is done through interviews and observation of the object of the research. The techniques of analysis employed in this research are the source triangulation technique, the pattern matching technique and qualitative descriptive technique which narrates the results of the interviews and observations.The result of this research shows that BMT Mandiri Sejahtera has positively strengthened the capital of micro, small and medium businesses, such is shown by the increase of income, profit, assets and capital structure after receiving funding from BMT Mandiri Sejahtera.